2006
DOI: 10.1016/j.tsf.2006.02.099
|View full text |Cite
|
Sign up to set email alerts
|

Etch rate and surface morphology of polycrystalline β-silicon carbide using chlorine trifluoride gas

Abstract: The etch rate of the polycrystalline β-silicon carbide (SiC) substrate in a wide range from less than one to more than ten µm/min is studied using chlorine trifluoride gas at concentrations of 10-100% in ambient nitrogen at 673-973K and atmospheric pressure in a horizontal reactor. The etch rate immediately increases at the substrate temperatures between 673 and 773K over the chlorine trifluoride gas concentrations used in this study. Additionally, the etch rate at higher than 773K is independent of the substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…This reactor has a small cross section above the substrate in order to achieve a very high consumption efficiency of the chlorine trifluoride gas. The height and the width of the quartz chamber are 10mm and 40mm, respectively, similar to our previous studies (7)(8)(9)(10)(11). A 30 mm wide × 50 mm long × 0.2 mm thick polycrystalline 3C-SiC wafer produced by the chemical vapor deposition method (Admap Inc., Tokyo) was horizontally held on the bottom wall of the quartz chamber as the susceptor.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…This reactor has a small cross section above the substrate in order to achieve a very high consumption efficiency of the chlorine trifluoride gas. The height and the width of the quartz chamber are 10mm and 40mm, respectively, similar to our previous studies (7)(8)(9)(10)(11). A 30 mm wide × 50 mm long × 0.2 mm thick polycrystalline 3C-SiC wafer produced by the chemical vapor deposition method (Admap Inc., Tokyo) was horizontally held on the bottom wall of the quartz chamber as the susceptor.…”
Section: Methodssupporting
confidence: 63%
“…For this purpose, chlorine trifluoride gas was first used for the polycrystalline 3C-SiC dry etching in our previous studies (7,8), because this gas has a very strong capability to etch various materials, such as silicon at a very high etch rate at room temperature (9). The etch rate of the polycrystalline 3C-SiC was greater than 20 um/min at temperatures above 723K and at the chlorine trifluoride gas concentration of 100 %.…”
Section: Introductionmentioning
confidence: 99%
“…The Si-face etch rate becomes greater than 7 um/min and maintains its value at substrate temperatures greater than 773 K in the reactor used in this study. Although the etch rate at the chlorine trifluoride gas flow rate of 200 sccm was not measured at the lower temperatures, the trend in the flat etch rate at the higher temperatures and the small etch rate at the lower temperatures is considered to be the same as that at 100 sccm and that for the polycrystalline 3C-SiC [1,2]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the authors have developed a chemical etching method of SiC using chlorine trifluoride gas (2)(3)(4)(5)(6)(7). Our previous Study (7) showed that the etch pits formed at low temperatures might have a relationship with dislocations.…”
Section: Introductionmentioning
confidence: 99%